2005
DOI: 10.5713/ajas.2005.1655
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profiles of Various Muscles and Adipose Tissues from Fattening Horses in Comparison with Beef Cattle and Pigs

Abstract: The present studies were designed to provide new information on fatty acid profiles of various muscles and adipose tissues of fattening horses in comparison with beef cattle and pigs. In the first study, the lipids were extracted respectively from subcutaneous, intermuscular adipose tissues, longissimus dorsi and biceps femoris muscles of fattening Breton horses (n = 8) with an average body weight of 1,124 kg. In the second study, the lipids were extracted from subcutaneous, intermuscular adipose tissues and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 22 publications
(26 reference statements)
7
27
2
2
Order By: Relevance
“…Generally the transfer of dietary omega-3 fatty acids to animal tissues in non-ruminants is more efficient than ruminants due to hydrogenation of unsaturated fatty acids by rumen microorganisms. Even horse adipose tissues contain much higher concentrations of omega-3 fatty acids than beef cattle when these herbivores are fed similar diets [31].…”
Section: Discussionmentioning
confidence: 99%
“…Generally the transfer of dietary omega-3 fatty acids to animal tissues in non-ruminants is more efficient than ruminants due to hydrogenation of unsaturated fatty acids by rumen microorganisms. Even horse adipose tissues contain much higher concentrations of omega-3 fatty acids than beef cattle when these herbivores are fed similar diets [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PLRP2 is absent in pigs, turkeys and ruminants but surprisingly present in horses (De Caro et al, 2008). This enzyme could potentially explain the high content of LNA deposition in horse tissues in comparison to porcine and poultry tissues (He, Ishikawa, & Hidari, 2005;Ribeiro et al, 2013). Based on the studies by Lorenzo, Fuciños, Purriños, and Franco (2010) and Guil-Guerrero et al (2013a) a large accumulation of LNA in horse tissues was evident when fed under extensive conditions (grass feeding) compared to animals finished with concentrates (3-5 kg/day for the last 3 months before slaughter (Table 2)).…”
Section: Digestive Physiology and Lipid Metabolism In Horsesmentioning
confidence: 91%
“…For footnotes see Table 3 Table 5 Concentration of FAME (g/100 g wet weight) and fatty acid profile (g/100 g total FAME) in the intramuscular fat of the M. quadriceps of rabbits fed different diets (n = 8 per group) However, as these processes in monogastric animals occur after the digesta has passed the duodenum, the major site of absorption for lipids, they do not have a major influence on the lipid composition of body tissues. This is reflected by higher proportions of PUFA in the tissues of horses, pigs and other hindgut fermenters as compared to ruminants and non-ruminant foregut fermenters [35][36][37][38]. Due to this dichotomy-absorption of 'ruminant-specific' FA in foregut fermenters, no absorption of such FA in hindgut fermenters-the endogenous presence of 'ruminant specific' FA has been considered as an indicator of foregut fermentation [39].…”
Section: Characteristics Of the Caecotroph Fatty Acid Profile And Efmentioning
confidence: 99%